(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article is devoted to the analysis of the structure of complex subordinate clauses expressing possessive relations in the Uzbek language, with an emphasis on their interpretation based on linguistic evidence.